Legal Regulation of Military Service in Ukraine by Foreigners and Stateless Persons (Law and Safety, 2025)
It is emphasised that today, along with its citizens, Ukraine is also being defended against russian aggression by citizens of other countries. Over the past three years, a number of amendments and additions have been made to national legislation regarding the legal status of foreign military personnel and stateless persons and the procedure for their military service.The points of view of scholars on the sectoral nature of military service relations are studied. The categories of “labour”, “service” and “contract” are considered. The close connection between the categories of “labour” and “service” is pointed out. It is substantiated that the category of “service” is manifested in the mental activity of an employee, which corresponds to one of the two types of employee’s activity, which can be physical and mental.It is proved that military service under a contract has the characteristics of non-independent, hired labour. Therefore, by its very nature, military service under a contract is a non-independent, specialised hired labour. The relations regarding the performance of military service under a contract are labour relations which are the subject matter of labour law.The attention is drawn to the fact that the Law of Ukraine “On Military Duty and Military Service” devotes only one article to the peculiarities of military service by foreigners and stateless persons (Article 21-2) and another article is devoted to their financial support (Article 21-3). The incorrectness of separate coverage of the procedure for financial support is pointed out, since it is an important condition for military service.Based on the analysis of Art. 21-2 of the Law of Ukraine “On Military Duty and Military Service”, it is noted that, despite the title, it has a rather laconic content, essentially not defining the specifics of military service by foreigners and stateless persons. The provision of Part 2 of Article 21-2 of this Law, which provides for the terms of military service of foreigners and stateless persons, cannot be called peculiar, since Article 23 “Terms of Military Service” provides for similar terms of military service in calendar terms for Ukrainian citizens who are enlisted for military service under a contract. The provision on the possibility of termination of the contract is hardly related to the performance of service. The article proposes to amend Article 21-2 “Peculiarities of Military Service by Foreigners and Stateless Persons” of the Law of Ukraine “On Military Duty and Military Service” to provide for differences in the rights, duties and responsibilities, terms of service, service time and rest time, and financial support of foreign military personnel and stateless persons compared to military personnel who are citizens of Ukraine.
Keywords: legal regulation; military service; foreigner; stateless person; serviceman; labour; employee; contract.